1969
DOI: 10.1017/s0424820100062440
|View full text |Cite
|
Sign up to set email alerts
|

Design and Application of a High Voltage Transmission Scanning Electron Microscope

Abstract: A transmission scanning electron microscope operating at voltages up to 600 kV has been built in this laboratory. Initial tests of the performance have been encouraging although the optimum performance has not yet been achieved. Developments and modifications of the instrument are now in progress in order to extend its range of applications and improve its output.The high voltage power supply and electron accelerator have been described previously. A combination of insulating oil and solid dielectric i s used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The success of Crewe's new STEM and the progressive improvement of image resolution in conventional TEM, from crystal lattice imaging (Menter, 1956;Dowell, 1963;Komoda, 1966;Allpress et al, 1969) to structural imaging (Iijima, 1971;Cowley & Iijima, 1972;Allpress & Sanders, 1973), clearly galvanized the excitement for developing high-voltage, high-resolution electron microscopes. Cowley and Strojnik started designing and building a 600-kV transmission scanning electron microscope and reported the initial results of their effort (Cowley & Strojnik, 1968, 1969Cowley, 1970;Cowley et al, 1970). In designing this high-voltage STEM, they used two lenses to form a small electron probe and added deflection systems to manipulate scattered electrons in order to obtain decent electron diffraction patterns and to direct the scattered electrons into the electron spectrometer for EELS analysis.…”
Section: The Emerging Stem Research and The Commercial Development Of Stemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The success of Crewe's new STEM and the progressive improvement of image resolution in conventional TEM, from crystal lattice imaging (Menter, 1956;Dowell, 1963;Komoda, 1966;Allpress et al, 1969) to structural imaging (Iijima, 1971;Cowley & Iijima, 1972;Allpress & Sanders, 1973), clearly galvanized the excitement for developing high-voltage, high-resolution electron microscopes. Cowley and Strojnik started designing and building a 600-kV transmission scanning electron microscope and reported the initial results of their effort (Cowley & Strojnik, 1968, 1969Cowley, 1970;Cowley et al, 1970). In designing this high-voltage STEM, they used two lenses to form a small electron probe and added deflection systems to manipulate scattered electrons in order to obtain decent electron diffraction patterns and to direct the scattered electrons into the electron spectrometer for EELS analysis.…”
Section: The Emerging Stem Research and The Commercial Development Of Stemsmentioning
confidence: 99%
“…If the scanning electron probe was stopped at any point of interest, a diffraction pattern, originating from a region with an area equal to the resolution limit of the STEM, would be recorded. In addition to investigating various STEM imaging modes, Cowley and colleagues studied the dependence of electron diffraction from crystalline samples on the defocus of the electron probe and discussed the origin of the fine structures in the observed convergent beam electron diffraction disks (Cowley et al, 1970;Smith & Cowley, 1971), similar to, but not exactly the same as, those reported for convergent beam electron diffraction (CBED) in conventional TEM (Cockayne et al, 1967). Cowley reported that the nature of the observed diffraction patterns depended on the aperture size of the probeforming lens and that the lens aberrations (e.g., spherical and chromatic aberrations) had an effect on the observed fine structures in the wide-angle CBED patterns.…”
Section: The Emerging Stem Research and The Commercial Development Of Stemsmentioning
confidence: 99%
See 1 more Smart Citation